1994
DOI: 10.1080/09595239400185751
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relationship between craving and relapse

Abstract: The value of craving as a construct in the substance use disorders literature stems from its purported ability to predict actual alcohol or psychoactive drug consumption. Empirical reports of craving's relationship to actual use, however, are quite mixed. It is argued that craving's relationship to use variables such as relapse will remain unclear until individual differences related to acting on craving are considered. Such potential mediators of craving's relationship to relapse, such as impulsivity, are eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…It is suggested that impulsivity may be a fundamental mechanism in relapse to substance use [14]. Also impulsivity was discussed as potential mediator of craving's relationship to relapse [75]. Consistent with this, our findings suggested that the craving has mediator effect on relationship between at least NPI dimension of impulsivity and relapse.…”
Section: Discussionsupporting
confidence: 86%
“…It is suggested that impulsivity may be a fundamental mechanism in relapse to substance use [14]. Also impulsivity was discussed as potential mediator of craving's relationship to relapse [75]. Consistent with this, our findings suggested that the craving has mediator effect on relationship between at least NPI dimension of impulsivity and relapse.…”
Section: Discussionsupporting
confidence: 86%
“…A brief review of the current literature would suggest that a more parsonomiuos view is that relapse is due to a direct correlation between high levels of craving and a higher risk of relapse in alcoholics [3642] including dopaminergic genetic antecedents including epigenetics [43]. …”
Section: Craving In Alcohol Use Disorder (Aud)mentioning
confidence: 99%
“…As “incentive cues” in drug abuse, Pavlovian–respondent relations are likely to be artifacts of operant functions rather than causal mediators of response–reinforcer relationships (R → S r+ ). This hypothesis may be especially true when considering that relapse does occur without cue-reactivity, and cue-reactivity does not always culminate in relapse (Drummond, 2001; Niaura et al, 1988; Rohsenhow & Monti, 1999; Tiffany & Carter, 1998; Tracy, 1994). If “craving” (i.e., cue-reactivity) is evoked by Pavlovian processes, and craving is not always correlated with relapse, then a Pavlovian interpretation alone cannot account for relapse and cue-reactivity.…”
Section: An Operant Analysis Of the Drug-taking Ritual In Cet: The Hementioning
confidence: 99%